2019
DOI: 10.1021/acs.jpcc.9b01630
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Electronic and Optical Properties of a Planar Hydrogenated AsSi Hybrid Nanosheet: A Potential Wide Water-Splitting Photocatalyst

Abstract: Two-dimensional (2D) layered structures have recently drawn worldwide attention in material science and device physics because of their intriguing electrical and optical properties. In this paper, the structural, electronic, and magnetic properties of fully and partially hydrogenated AsSi nanosheets (NSs) are investigated by first-principles calculations based on density functional theory. Moreover, the potential as photocatalysts for water splitting is also studied. The results demonstrate that hydrogenated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…[ 46 ] The AsSi nanosheet was another candidate for this reaction. [ 47 ] It was demonstrated that AsSiH NSs with tensile strains up to 9% exhibit proper bandgaps, valence, and CB positions of the reduction and oxidation levels in visible light‐driven water splitting. [ 47 ]…”
Section: Catalytic Applications Of 2d Simentioning
confidence: 99%
“…[ 46 ] The AsSi nanosheet was another candidate for this reaction. [ 47 ] It was demonstrated that AsSiH NSs with tensile strains up to 9% exhibit proper bandgaps, valence, and CB positions of the reduction and oxidation levels in visible light‐driven water splitting. [ 47 ]…”
Section: Catalytic Applications Of 2d Simentioning
confidence: 99%
“…Hydrogenation can signicantly change the properties of 2D materials and is reported to have potential applications in spintronic devices. [26][27][28][29] Theoretical predictions have revealed hydrogenation is an effective method to tailor the electronic properties of 2D silicene-related materials, and some of them have been observed in the experiments. [30][31][32][33][34][35][36][37][38][39] Recent studies have reported fully hydrogenated silicene becomes wide band gap semiconductor and the type of gap depending on its atomic conformation, 31 whereas half hydrogenated silicene transforms to ferromagnetic semiconductor.…”
Section: Introductionmentioning
confidence: 99%